The 123 agreement – strengthening non-proliferation in Southeast Asia - Chew, Alvin (2024)
Singapore signed a landmark 123 Agreement for peaceful nuclear cooperation with the US to strengthen the regional non-proliferation and nuclear security landscape. The agreement is timely given the growing interest in civilian nuclear energy programmes in Southeast Asia.